Copolymerization of 2‐isothiocyanatoethyl methacrylate and 2‐hydroxyethyl methacrylate or methacrylic acid based on a nucleophile‐tolerant property of the isothiocyanato group. Issue 24 (8th October 2013) - Seto, Ryota; Matsumoto, Kozo; Endo, Takeshi
ABSTRACT Radical copolymerizations of 2‐isothiocyanatoethyl methacrylate (ITEMA) and 2‐hydroxyethyl methacrylate (HEMA) or methacrylic acid (MAA) were examined, and fundamental properties of the obtained copolymers were investigated. The copolymerizations of various ITEMA/HEMA or ITEMA/MAA compositions proceeded effectively in THF or DMF by using 2, 2′‐azobisbutyronitrile (AIBN) as an initiator, keeping the isothiocyanato groups and hydroxyl or carboxyl groups unchanged. Glass transition temperatures (Tg)s of poly(ITEMA‐co‐HEMA)s ranged from 68 to 100 °C, and they were thermally stable up to 200 °C. Meanwhile, Tgs of poly(ITEMA‐co‐MAA)s (ITEMA/MAA = 91/9, 76/24) were determined to be 91 and 109 °C, respectively. However, poly(ITEMA‐co‐MAA)s were thermally unstable, and significant weight loss was observed around 180 °C, which may be due to an addition of carboxyl groups to isothiocyanato groups followed by an elimination of COS to form amide structure in the copolymers. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 5221–5229